Predictors of attitudes towards dating violence in higher education students: The role of emotional intelligence and self-esteem - Silva, Tânia Andrade da (2021)
Dating violence is an important problem among Portuguese young people, following international trends in this domain. The present study aims to understand how emotional intelligence can influence higher education students’ attitudes towards dating violence, while exploring the mediating role of self-esteem in this relation, as well as gender differences. Participants were 555 higher education students, 62% female and 38% male, with ages between 18 and 25 years (M = 20.76, SD = 1.87). The main results show gender differences in the relations between the analyzed variables. In the female students, emotional intelligence is negatively related to attitudes towards dating violence due to the mediator role of self-esteem. In male students there is a direct and negative effect of emotional intelligence on attitudes towards dating violence. Emotional intelligence has more influence for male students and self-esteem for female students. Therefore, future interventions should focus on these variables for each gender in order to prevent the acceptance of dating violence and, consequently, dating violence.